Jerome: Vita malchi introduction, text, translation, and commentary - Hieronymus, Sophronius Eusebius 345-420 (Oxford classical monographs, 2017)
A full translation and analysis of one of the more intriguing works by a figure who is central to our understanding of late antiquity and early Christianity: the translator, exegete, and controversialist Jerome (c.347-419/20AD)